Penerapan Model Pembelajaran Cooperatif Learning dalam Meningkatkan Kompetensi Paedagogik Guru Matematika Kelas VI melalui Pembinaan Pengawasan di Kecamatan Sekongkang Tahun Pelajaran 2019-2020 - Wahiddin (Jurnal LENTERA: Jurnal Studi Pendidikan, 2020)
This supervisory action research (PTKp) aims to find out the extent of supervisors' guidance to improve the ability of teachers to apply cooperative learning models of mathematics learning for VI-grade elementary school in Sekongkang District. In the supervisory action research (PTKp) is carried out in 3 cycles, the results of the actions taken are proven to be able to improve teacher performance by achieving ideal standards. From 58.89% in the first cycle, it can increase to 69.33% in the second cycle, and the third cycle 77.89%. The results of this action research show that supervisors can improve teacher performance in developing cooperative learning of elementary school sixth- grade mathematics learning with completeness reaching 100%.